Timor-Leste: reforming the education system through school leader capacity building and school-based teacher professional development. Issue 1 (2nd January 2021) - Owen, Susanne; Wong, Debbie
ABSTRACT: After decades of conflict with Indonesia, Timor-Leste is gradually rebuilding its education infrastructure and reclaiming its identity as an independent country. In the first decade post-independence the education sector faced many challenges, including a lack of school buildings and resources, the need to replenish and upskill the Timorese teacher workforce, and inappropriate curriculum. In more recent years, a locally written child-centred curriculum has been rolled out and a systematic and ongoing school leadership and teacher professional development programme has gradually been established. The programme requires school leaders to support ongoing teacher professional development, and to participate in regular mentor visits. The underlying change model focuses on school leader capacity building, so principals work with their teachers to improve their classroom skills, with resultant impact on student learning. This article provides details of the leadership programme and reports some results for the school regions initially involved regarding leader and teacher skills improvement and student learning outcomes. The results provide early indications of the value for developing countries of a leadership capacity-building and school-based teacher professional development programme which involves a whole-of-system approach and ongoing mentor support and monitoring.